The role of accounting variables in valuation of banks - Bolibok, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper aims at assessment of the role of accounting variables in the valuation of banks. The study is based on the review of existing literature on the theoretical frameworks of bank valuation with a particular focus on their practical applicability, and the value relevance of accounting variables in the banking sector. The results of the research indicate that an idiosyncratic nature of banking activities and their recognition in accounting ledgers render the informational content of banks’ financial statements particularly useful for valuation purposes. The investigation allowed to identify a comprehensive set of key value drivers determined by the accounting variables available in banks’ financial reports, and to propose a conceptual model of their linkages to bank value under the major practically applied bank valuation techniques
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 479, s. 23-33
Keywords: banks; valuation; accounting information; financial reporting; banki; wycena; informacje z systemu rachunkowości; sprawozdawczość finansowa